Pelatihan Simulasi Dynamic Routing dan Virtual Lan Untuk Jaringan Menggunakan Cisco Packet Tracer Bagi Siswa Magang di PT. Jembatan Data Pangranggo (JDP) Lombok Timur - Muhamad Aditya Ananda; Wire Bagye; Sofiansyah Fadli (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Training "Dynamic Routing and Virtual LAN Simulation for Networks Using Cisco Packet Tracer" at PT. The Pangranggo Data Bridge (JDP) East Lombok aims to increase the knowledge and skills of apprentice students in the field of computer networks. In this training, participants from the Computer and Network Engineering department were introduced to the basics of networking, dynamic routing, and VLANs using Cisco Packet Tracer as a simulation tool. Through a learning method that includes preparation, implementation and evaluation for seven days, this training succeeded in strengthening theoretical understanding and increasing participants' practical abilities in network configuration. Evaluation results show significant improvements in mastery of dynamic routing and VLAN concepts, preparing participants for challenges in the world of work with relevant practical skills. This training also contributes to the development of a more efficient and integrated network infrastructure